Contingency, behavioural and evolutionary perspectives on public and non-profit governance - Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Studies in public and non-profit governance ;, 2015)
This volume assesses governance in public and non-profit organizations. Building on and challenging recent research in this area, this volume critically examines the contextual, behavioural and historical factors of governance. Topics include; the role, behaviour and effectiveness of a board of directors; the relationships between board members and stakeholders; innovations in governance; accountability, transparency and integrity of governance; measuring and assessing organizational performance and new forms of governance arrangements in service provision.